(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The most fragmented area on the globe is the South Pacific. It is dotted with small to broad island nations and dependencies, with a number of more than two thousand four hundred. The smallest government units in the world are each of these nations. Australia, by comparison, is a continental nation (7.6 million sq. km.) in area. Nauru is the smallest republic in the country, with a meager territory of 21 sq. Km. Politically, the region ’s real promise resides in the large array of coastal waters and exclusive economic zones with an immense resource base. The greatest recipients of the Rule of the Sea introduced in 1982 were the countries of the Pacific Islands. In several of these nations, mining has become a significant economic practice, e.g. copper and gold mining in Papua New Guinea, Solomon Islands and Fiji, phosphates in Nauru and Kiribati and natural gas in Papua New Guinea. Since the 1970s, the ’pacific route’ a term popularized by Fiji’s Ratu Mara has become used to demonstrate the nature of the Pacific and their consensual attitude to coping with the reg.